Correlation Between Small Dense Low-Density Lipoprotein and Risk Factor Cardiovascular on Obesity (TALENTA Publisher, Universitas Sumatera Utara, 2022)
Background: Small dense low-density lipoprotein concentration (sdLDLC) subclasses are smaller in volume than other LDL types, they have a greater propensity for endothelial penetration and subsequent atherogenesis. The objectives of the study assessed the relationship between sdLDLC and cardiovascular risk in obesity Method: This cross-sectional study was conducted on obesity. Informed written consent was obtained after explaining the nature of the study to the patients, and ethical clearance was obtained. Body mass index (BMI) was measured using standard methods. Laboratory assessment included venous blood samples in a fasted state for the determination of components of the lipid profile [total cholesterol (TC), HDL-C, and TG], ApoB, and sdLDL. The serum glucose was measured using the glucose oxidase/peroxidase method and the lipid profile by the enzymatic colorimetric method. LDL-C was calculated from the formula of Friedewald. Result: This study included 40 obese patients with a BMI of 33.14Â±5.00 kg/m2, the age of 41.75Â± 6.02 years old. There was a significant correlation between sdLDL with age, BMI, FPG, PPG, and TG (p < 0.05). Conclusion: There is a significant between sdLDL with risk factors cardiovascular of profile lipid and profile glucose.